POLÍTICAS PÚBLICAS DA EDUCAÇÃO PROFISSIONAL TÉCNICA DE NÍVEL MÉDIO NA 10ª COORDENADORIA REGIONAL DE EDUCAÇÃO DO RIO GRANDE DO SUL - Saldanha Júnior, Marco Antônio Souza (2023)
The present research, entitled “Public Policies of Technical Professional Education of Medium Level in the 10th Regional Coordination of Education”, aims to understand the context of the courses of Professional Technical Education of Medium Level offered by the government of the State of Rio Grande do Sul with a focus on at the 10th Regional Education Coordination. In order to meet the proposed objective, we will follow the following specific objectives: Map the courses of Technical Professional Education of Medium Level offered by the government of the State of Rio Grande do Sul, with emphasis on the distribution of technological axes in the municipalities and in the Regional Coordination of Education; Discuss the training itinerary: professional technical training and public policies for the implementation of the new secondary education; to investigate the offer and demand of courses of Technical Professional Education of Medium Level made available by the government of the State of Rio Grande do Sul, specifically by the 10th Regional Coordination of Education; and Check which proposals for the Medium Level Technical Professional Education courses the government of the State of Rio Grande do Sul intends to implement in order to keep up with the technological context. In this sense, we have the following question that guided the research: Is the offer of Technical Professional Education courses offered by the government of the State of Rio Grande do Sul in the 10th Regional Coordination of Education adequate to the current technological context? This research focuses on the context of Middle Level Technical Professional Education courses provided by the government of the State of Rio Grande do Sul, emphasizing supply, demand and possibilities in the face of the current technological scenario. The research is justified by the need to understand the reality of the EPT in the 10th CRE, in order to indicate mechanisms for the expansion and qualification of the courses offered. The methodological approach of the research is qualitative, using bibliographical and documentary data, as well as data collected through individual, semi-structured open-ended qualitative interviews with agents who perform management functions with the state education network. Professional and Technological Education is an educational modality that aims to facilitate the insertion and performance of students in the world of work. The courses range from training courses, improvement and updating of citizens, to the courses of the professional and technological master's and doctoral programs, passing through the focus of this research the courses of Technical Professional Education of Medium Level, the current technological context is dynamic and requires constant updating of EPT courses so that they are aligned with the needs of the labor market and the demands of society in terms of innovation and technology. In this sense, it is essential that the management of professional and technical education policies in Rio Grande do Sul is attentive to changes in the world of work and new technological demands, promoting the continuous updating and adaptation of EPT courses.